Implementation of Discovery Learning to Increase Student Activeness in Aqidah Akhlak Lessons at MI Maarif NU Darul Ulum Ranupakis - Kholifah, Yeni; Puteri, Yayuk Sri Rahma; Yanti, Yeyeng; Yatimah (ETNOPEDAGOGI: Jurnal Pendidikan dan Kebudayaan, 2024)
This study aims to analyze the application of the Discovery Learning model in improving student activity in the subject of Akidah Akhlak in class V MI Ma'arif NU Darul Ulum Ranupakis. Discovery Learning is a learning method that emphasizes the active involvement of students in finding concepts independently through exploration, investigation, and problem solving. This study uses a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation to determine the effectiveness of this model in improving student activity. The results of the study indicate that the application of Discovery Learning can improve student activity in several aspects, such as active participation in discussions, courage to express opinions, and the ability to think critically and independently in understanding the material. In addition, this method also encourages students to be more enthusiastic in participating in learning, increases interaction between students and teachers, and creates a more dynamic learning atmosphere. The obstacles found include student readiness in learning independently and limited time in the learning process. However, with the right teacher guidance, Discovery Learning has proven to be an effective learning model to improve student activity and understanding of the Akidah Akhlak material.